2014
DOI: 10.1093/gbe/evu125
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin and Methylation Status of Human Intronic CpG Islands that Are Not Present in Mouse

Abstract: Imprinting of the human RB1 gene is due to the presence of a differentially methylated CpG island (CGI) in intron 2, which is part of a retrocopy derived from the PPP1R26 gene on chromosome 9. The murine Rb1 gene does not have this retrocopy and is not imprinted. We have investigated whether the RB1/Rb1 locus is unique with respect to these differences. For this, we have compared the CGIs from human and mouse by in silico analyses. We have found that the human genome does not only contain more CGIs than the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…37 Rademacher et al reported that the human genome contains at least 2,000 intronic CpG islands that are not present in the mouse genome, a subset of which show sequence similarities elsewhere in the human genome, suggesting that they arose via retrotransposition. 38 Transposable elements, such as the murine A vy metastable epiallele, have been previously implicated as targets for early environmental effects on the epigenome. 39 These data suggest that the human genome may contain a larger number of intronic epigenetic targets for environmental perturbation than rodents, indicating the importance of including intronic targets in studies evaluating the impact of environmental epigenetics on human health.…”
Section: Assay Forward Primermentioning
confidence: 99%
“…37 Rademacher et al reported that the human genome contains at least 2,000 intronic CpG islands that are not present in the mouse genome, a subset of which show sequence similarities elsewhere in the human genome, suggesting that they arose via retrotransposition. 38 Transposable elements, such as the murine A vy metastable epiallele, have been previously implicated as targets for early environmental effects on the epigenome. 39 These data suggest that the human genome may contain a larger number of intronic epigenetic targets for environmental perturbation than rodents, indicating the importance of including intronic targets in studies evaluating the impact of environmental epigenetics on human health.…”
Section: Assay Forward Primermentioning
confidence: 99%
“…20 By comparing the position of CGIs and retrocopies using the Perl programming language (http://www.perl.org/), all CGIs overlapping a retrocopy were determined. To divide CGIs/retrocopies in intergenic and intragenic once, we compared the positions of all CGIs/retrocopies to the positions of RefSeq genes.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Rademacher et human/non-murine intronic CGIs reported previously by Rademacher et al 20 In addition to monocytes, we analyzed the newly discovered 17 CGIs/retrocopies in an additional methylome data set (Rademacher et al; EGA accession: EGAS000001000719), 16 already published methylome data sets by Ziller et al and two oocyte methylome data sets published by Okae et al (Table S8). [20][21][22] Out of these 17 CGIs/retrocopies, seven CGIs (2391_1_hg19, 9224_1_hg19, 9261_1_hg19, 9377_1_hg19, 17031_1_hg19, 23548_1_hg19 and 24982_1_hg19) showed an intermediate methylation level in nearly all tissues except for human sperm DNA, where all CGIs are typically unmethylated. No methylation in nearly all tissues was found in three CGIs (13250_1_hg19, 16458_1_hg19, and 20403_1_hg19), six CGIs are fully methylated in at least three tissues, and one CGI (6141_1_hg19) is not methylated in fetal tissues.…”
Section: Search For Allele-specific Methylationmentioning
confidence: 99%
See 2 more Smart Citations